The eloquent president : a portrait of Lincoln through his words. - White, Ronald C. Jr., ....- (New York : Random House, 2006)
The fact that Abraham Lincoln is now universally recognized as America's greatest political orator would have surprised many of the citizens who voted him into office. Ungainly in stature and awkward in manner, the newly elected Lincoln was considered a Western stump speaker and debater devoid of rhetorical polish. Then, after the outbreak of the Civil War, he stood before the nation to deliver his Message to Congress in Special Session on July 4, 1861, and, as a contemporary editor put it, "some of us who doubted were wrong." In The Eloquent President, historian Ronald White examines Lincoln's astonishing oratory and explores his growth as a leader, a communicator, and a man of deepening spiritual conviction. Examining a different speech, address, or public letter in each chapter, White tracks the evolution of Lincoln's rhetoric from the measured, lawyerly tones of the First Inaugural, to the imaginative daring of the 1862 Annual Message to Congress, to the haunting, immortal poetry of
The Gettysburg Address. As a speaker who appealed not to intellect alone, but also to the hearts and souls of citizens, Lincoln persuaded the nation to follow him during the darkest years of the Civil War. Through the speeches and what surrounded them-the great battles and political crises, the president's private anguish and despair, the impact of his words on the public, the press, and the nation at war-we see the full sweep and meaning of the Lincoln presidency. As he weighs the biblical cadences and vigorous parallel structures that make Lincoln's rhetoric soar, White identifies a passionate religious strain that most historians have overlooked. It is White's contention that as president Lincoln not only grew into an inspiring leader and determined commander in chief, but also embarked on a spiritual odyssey that led to a profound understanding of the relationship between human action and divine will. Brilliantly written, boldly original in conception, The Eloquent President blends history
Biography, and a deep intuitive appreciation for the quality of Lincoln's extraordinary mind. With grace and insight, White captures the essence of the four most critical years of Lincoln's life and makes the great words live for our time in all their power and beauty.
Keywords: Verenigde Staten -- Geschiedenis; Verenigde Staten -- Politiek